2016
DOI: 10.1111/cyt.12384
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda classification is a valuable guide for fine needle aspiration reports and highly predictive especially for diagnosing aggressive variants of papillary thyroid carcinoma

Abstract: The Bethesda classification is a reliable indicator of malignancy in nodules with different cytology results and seems to be very effective in predicting the malignancy for the nodules diagnosed with aggressive variant PTC on the final histological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
2
32
2
1
Order By: Relevance
“…Liu et al from the USA concluded that the Bethesda cytological categories successfully stratify patients based on their observation that recurrence, distant metastases and death increased as cytology progressed from AUS/FLUS to SM to malignant categories. Evranos et al from Turkey reported that SM or malignant cytological diagnoses were more often given to aggressive variant PTC (92.0%) and conventional PTC (56.6%), but less frequently to follicular variant PTC (24.3%). However, the authors of this article attribute all these observations and conclusions to the fact that significant numbers of borderline/precursor tumours were classified in the AUS/FLUS, FN/SFN and SM categories, and that they were included as malignant tumours.…”
Section: Prognosis Of Thyroid Carcinomas In Indeterminate Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al from the USA concluded that the Bethesda cytological categories successfully stratify patients based on their observation that recurrence, distant metastases and death increased as cytology progressed from AUS/FLUS to SM to malignant categories. Evranos et al from Turkey reported that SM or malignant cytological diagnoses were more often given to aggressive variant PTC (92.0%) and conventional PTC (56.6%), but less frequently to follicular variant PTC (24.3%). However, the authors of this article attribute all these observations and conclusions to the fact that significant numbers of borderline/precursor tumours were classified in the AUS/FLUS, FN/SFN and SM categories, and that they were included as malignant tumours.…”
Section: Prognosis Of Thyroid Carcinomas In Indeterminate Categoriesmentioning
confidence: 99%
“…FT-UMP (10) As the majority of cases with indeterminate cytology are benign or borderline tumours, and the majority of thyroid carcinomas in indeterminate categories were low-risk, [49][50][51][52] clinical follow-up of these nodules is one method recommended by the JTA clinical guidelines as long as they have benign clinical features. 16,17,45 Proper better risk stratification of thyroid cancer, which is a common practice in Asia.…”
Section: Thyroid Fnac In Asiamentioning
confidence: 99%
“…The neoplastic cells are elongated with distinct cell borders and apically placed and protruding “hobnailed” nuclei. Nuclear features of PTC are often present …”
Section: Discussionmentioning
confidence: 99%
“…The variants have been described based on size, nature of tumor boundaries, architecture, cellular characteristics, stromal features or a combination of the above mentioned characteristics . PTC is considered a well differentiated neoplasm; however, some of its variants are known to have an aggressive clinical course and imply poor prognosis . However, poorly differentiated carcinoma of the thyroid is characterized by solid, insular and/or scirrhous growth pattern with increased mitoses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation